Pelatihan Assessment Badan Pendapatan Daerah Kabupaten Berau - Djupiansyah Ganie; Muhammad Bayu; Darmono Darmono; Nahwani Fadelan; Sayugo Adi Purwanto; Siti Munawaroh; Hasbiah Hasbiah (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
The Assessment Training conducted by the Regional Revenue Agency (Bapenda) of Berau Regency is a strategic effort aimed at enhancing the competency of civil servants in objectively and systematically evaluating employee performance. This training was designed to provide participants with a solid understanding of basic assessment concepts, techniques for developing performance indicators, and the practical application of evaluation methods relevant to their respective roles and responsibilities. The training methods included lectures, interactive discussions, and hands-on simulations in assessment design and implementation. The results of the training indicate improved participant understanding of the importance of performance assessment as a basis for managerial decision-making, employee development, and organizational capacity building. This initiative is expected to contribute to the creation of a more professional, transparent, and accountable system for managing regional revenue through improved human resource quality within Bapenda Berau.